PERBANDINGAN PERFORMANSI AIR CONDITIONING HIBRIDA PADA STANDBY MODE (TRADITIONAL AC) DENGAN BEBAN PENDINGINAN 1000 WATT DAN TANPA BEBAN PENDINGINAN - Azridjal Aziz; Eko Prasetyo; Rahmat Iman Mainil (Jurnal Sains dan Teknologi, 2020)
AbstractThe experimental study of a hybrid AC (Air Conditioning) system (utilizing both cooling and heating sides) in standby mode (traditional AC) operated without cooling load and with 1000 Watt cooling load has been carried out in this study. Hybrid AC performance without load compared to condition with a load of 1000W had the average COP (Coefficient of Performance) of around 2.460 versus 2.452, PF (Performance Factor) of around 3.42 versus 3.41 and TP (Total Performance) of around 5.88 versus 5 .86, respectively. The test results showed that by using cooling load of 1000 Watt, could provide an average cooling room temperature of 28.3 °C, a heating room temperature of 44.9 °C, a compressor power of 0.5825 kW while the result of without cooling load condition, the temperature of the cool room was average 22.5 °C, heating room temperature of 38.8 °C, compressor work of 0.5449 kW. The test results of the AC hybrid machine with HCR-22 refrigerant showed that the condition of without cooling load had a performance that was little bit different compared to the cooling load of 1000W. This results showed that the temperature of the cold room with a cooling load of 1000 Watt made the temperature of the cold room was uncomfortable for human, so that the cooling load must be reduced or the cooling capacity must be increased.